Local Based Educational Tourism Development Strategy Management in East Java - Rachmaniar Rachmaniar; Renata Anisa (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the strategic management of local-based educational tourism development in East Java Province through a literature review of three empirical studies conducted in Bojonegoro , Kediri, and Blitar . Educational tourism is defined as a form of travel that focuses not only on leisure but also on learning, cultural preservation, and the empowerment of local economies. The method used in this research is a literature review, with content analysis of three selected academic articles and a strategic mapping based on strategic management theory and national tourism development policies. The findings indicate that each region applies a different approach to developing educational tourism, yet all emphasize the importance of collaboration between local governments, communities, and the private sector. In Bojonegoro , the development strategy struggles at the implementation and evaluation stages; in Kediri, a step-by-step and comprehensive model is evident; whereas in Blitar , adaptive strategies and creative promotion serve as key drivers for post-pandemic recovery. The success of educational tourism management is strongly influenced by the utilization of local assets, targeted digital promotion, institutional strengthening (such as community-based tourism groups), and continuous evaluation and innovation. This study is expected to contribute both practically and theoretically to the development of educational tourism in Indonesia. It also emphasizes that strategic management in educational tourism must be dynamic, locally grounded, and capable of addressing socio-economic challenges in a contextual and sustainable manner.